Development of a personality recognition system by voice (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2020)
Abstract— the paper discusses the development of a voice recognition system based on cepstral coefficients on the chalk scale (Mel-frequency Cepstral Coefficients, MFCC) and mixed Gaussian models (Gaussian Mixture Models, GMM). The aim of the research is to create a simple and convenient automatic speaker recognition system. The description of the created speech database for the Kazakh language is given. Experiments have shown quite good results of the system FAR 8.05%.
Keywords: voice recognition system; MFCC; GMM; speech database